Sinoicismo y stolati en Emerita, Caesaraugusta y Pax: Una relectura de Estrabón III, 2, 15 - Canto, Alicia M.ª (Gerión. Revista de Historia Antigua, 2001)
Once again, this work calls into question some of the more traditional translations which have been largely accepted by historians and archaeologists alike, but have led to errors. The text I’m examining now, Estrabon III, 2, 15, is one of the best known and most quoted in all Spanish Ancient History. The seven changes now put forward allow for many new points of view. The generally accepted word «togátoi» (from Kramer, 1844) should most definitely be rejected in this paragraph and also in III, 4, 20. The natives described are really «stolátoi», but not all their tribes however; only the ones chosen for sinoikismus. In fact, throughout this paragraph, Estrabon is praising the Latinisation of these territories, and not their romanisation. For Estrabon the three cities mentioned (Caesaraugusta, Eme- rita and Paxaugusta) are póleis or katoikíai, but not apoikíai; therefore they cannot be coloniae ex novo, but pre existing municipia, mixed and with strong military contingents. The dates believed for their possible colonisation conflict with those suggested by Augustus in his Res Gestae: the years 30, 14 o 7-2 B.C. Finally, a possible explanation for the physical appearance of these stolátoi, possibly cives Latini: the statues and bas-reliefs of men dressed in the so-called pallium or toga exigua, until now, in Spain as in Italy and Rome, classified as palliati.